Effective medium ratio obeying metamaterial absorber for 5G sub-7 GHz and sub-8 GHz applications - Jakir Hossain, Mohammad; Uddin, Md. Alim; Islam, Md. Mesbahul; Ghosh, Keya; Jahan, Nusrat; Akter Asma, Mukta (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Metamaterials possess the capability to enhance fifth-generation (5G) communication technology. This article proposes an innovative construction of a miniature metamaterial absorber (MMA) with a dramatically improved effective medium ratio (EMR) characterized by utilizing a multi-square split-ring resonator (MSSRR) MMA unit cell specifically designed for operation in the 5G sub-7 GHz and Sub-8 GHz frequency bands. The unit cell of the MMA is designed using a commercially available FR-4 material with εr=4.3, which is cost-effective. The proposed MMA achieves a remarkably high EMR of 9.83, indicating superior compactness and design efficiency. The MMA of interest operates with absorbance peaks of 70.632%, 96.936%, and 79.930% within the frequencies of 3.554 GHz, 4.940 GHz, and 8.335 GHz, respectively. Along with the absorption analysis, our examination also includes E-field, H-field, surface current, and power flow. The expected MMA has proven potential for application in some frequency bands related to 5G, released absorption signal, and specific absorption rate (SAR) assistance.